Solving Fuzzy Fractional Differential Equations Using Zadeh's Extension Principle - M. Z. Ahmad; M. K. Hasan; S. Abbasbandy (The Scientific World Journal)
We study a fuzzy fractional differential equation (FFDE) and present its solution using Zadeh’s extension principle. The proposed study extends the case of fuzzy differential equations of integer order. We also propose a numerical method to approximate the solution of FFDEs. To solve nonlinear problems, the proposed numerical method is then incorporated into an unconstrained optimisation technique. Several numerical examples are provided.